AI Adoption and Strategic Decision-Making Transformation in Thai Companies - Aminah Chesoh (Universitas Muhammadiyah Jember, 2026)
The rapid expansion of artificial intelligence (AI) in organizational environments has transformed how companies formulate and execute strategic decisions, particularly in Thailand’s increasingly competitive digital economy. As organizations face growing pressure to integrate AI into managerial processes, understanding its influence on strategic decision-making has become increasingly important. This study aims to explore how AI adoption reshapes strategic decision-making practices in Thai companies and to examine the organizational and governance implications associated with this transformation. Using a qualitative exploratory case study approach, data were collected through in-depth interviews with key organizational actors, supported by document analysis and observations. The findings reveal that AI adoption facilitates a shift toward more adaptive and data-driven decision-making by integrating algorithmic analytics with human judgment, enhancing organizational learning, and improving cross-functional information flows. At the same time, the study identifies challenges related to data governance, algorithmic bias, and accountability that require stronger organizational oversight. The main contribution of this study lies in extending the socio-technical perspective of AI adoption by demonstrating how AI reshapes managerial cognition, decision-making authority, and governance structures within organizations in a Southeast Asian context. By providing qualitative evidence from Thai companies, this research offers a contextual understanding of AI-driven organizational transformation and highlights the importance of aligning technological innovation with responsible governance to sustain long-term organizational effectiveness and legitimacy.